Encouraging a Regional Autonomy in Indonesia: An Analysis of Factors Affecting the Own Source Revenue of Central Java Province - Susilowati, E; Rahmadewi, D E (KnE Social Sciences, 2018)
A provincial financial independence is one of indicators to implement regional autonomy. The existence of regional autonomy provides flexibility for local governments to manage resources and accountable to the community in a transparent, effective and efficient manner. The sources of financial independence are derived from the Own Source Revenue (PAD). In order to reduce the fund dependency, local governments should seek potential alternatives to increase its own source revenues. Therefore, the purpose of this study is to analyze the effect of capital expenditure, special allocation fund, inflation and financing expenditure on own source revenue in Central Java Province. Until recently, its the general allocation fund increases annually even though its own source revenue increases. The type of data applied was a secondary data from 2010 until 2014. An observation method was employed to collect data from the budget realization report published by the Ministry of Home Affairs, Ministry of Finance, and the Central Statistics Agency of Central Java. Data processing was carried out by employing multiple regression analysis. The findings indicated that significant factors affecting own source revenue of Central Java were capital expenditures (∝ 1%; coeff. = 0.690), inflation (∝ 5%; coeff. = 0,095), special allocation fund (∝ 10%; coeff. = -0.093), and financing expenditure (∝ 1%; coeff. = 0.424). Further managerial implications were discussed. Keywords: Decentralization, Regional Autonomy, Local Revenue, General Allocation Fund, Own Source Revenue